Oligo-Glucomannan Production from Porang (Amorphophallus oncophyllus) Glucomannan by Enzymatic Hydrolisis Using β-Mannanase - Widiastuti Setyaningsih; Santad Wichienchot; Eni Harmayani; Anggela Anggela (Indonesian Association of Food Technologists, 2020)
Porang (Amorphophallus oncophyllus) is an indigenous tuber of Indonesia that rich in glucomannan. An alternative approach to produce porang oligo-glucomannan (POG) as prebiotic from porang glucomannan (PGM) was made by enzymatic hydrolysis using β-mannanase. This study aimed to produce POG under optimal conditions by controlled enzymatic hydrolysis process. The PGM flour contained 96.12% of indigestible carbohydrates. The optimum condition of enzymatic hydrolysis producing the highest reducing sugar was as follows: temperature 37 °C, pH 5.5, a ratio of enzyme to the substrate (E/S) 1:1000, and reaction time 4 h. HPLC analysis confirmed that 99.45% of the resulting POG consisted of oligosaccharides with a degree of polymerization (DP) 3. Hence, the PGM utilized in this study has been proven as a potential substrate for POG production. Additionally, the resulting POG was considered as a functional ingredient due to has prebiotic potential.